Profesionalisme Dokter dan Tanggung Jawab Medis: Perlindungan Pasien dan Upaya Hukum Perdata - Kamran, Muhammad; Syahrul, Syahrul (SIGn Jurnal Hukum, 2024)
This study aims to analyze physician professionalism and medical liability within the framework of civil law, particularly concerning patient protection and available legal remedies. Employing a normative legal research method and a statutory approach, this study examines relevant legal norms, primarily those contained in Law Number 8 of 1999, the Civil Code, and Law Number 17 of 2023. The data were analyzed prescriptively, not only to explain the prevailing law (das Sein) but also to formulate how the law should be applied or developed (das Sollen) in order to provide optimal legal protection for patients. The results indicate that physician professionalism, encompassing technical competence, moral integrity, and adherence to professional standards and medical ethics, is the basis for realizing quality and equitable healthcare services. Medical liability, which includes civil and criminal legal liability and ethical and moral responsibility, constitutes an important framework for establishing a balanced contractual relationship between physicians and patients. In medical malpractice, civil law instruments, specifically lawsuits based on breach of contract, tort, and negligence, provide avenues for patients to claim compensation for losses suffered and out-of-court dispute resolution mechanisms that need to be further encouraged.